Response to the Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care - Zientek, David M. (Christian bioethics, 2001)
David M. Zientek; Response to the Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care, Christian bioe